Ice Nucleation during Cell Cryopreservation: A Review - Jiang Pei; Huo Xiaoyue; Liu Baolin; Liu Wei; Liang Wei (Zhileng xuebao)
The major challenge to cell cryopreservation is intracellular ice formation (IIF), which can be reduced by controlling ice nucleation. In this review, the influence of ice nucleation on super-cooling and damage zone was analyzed. Physical, chemical, and biological methods have been applied to control ice nucleation during cryopreservation. The mechanisms of these methods were summarized and the influence of these methods on cell cryopreservation were discussed. Then it was proposed that biological and chemical methods should be superior methods of controlling ice nucleation. Additionally, the best ice seeding temperature was further proposed. At this temperature, ice crystals are initiated in the extracellular solution, which could result in minimal cell volume by reducing intracellularly active water properly, and then the incidence of IIF is reduced. The direction of ice seeding applied in the cell cryopreservation was pointed out.